Online Learning of Foreign Language Program in the Intensive Learning Class at the IAIN Padangsidimpuan Language Development Center - Amin, Irsal; Siregar, Khoiruddin Manahan; Minda, Sri (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
Pandemic learning forcibly moved from face-to-face learning into online learning. It makes teachers and learning transformation students IAIN Language Development Center Padangsidimpuan get a new challenge, they must master the teaching materials and teaching strategies as well as the need to master Technology internet-based learning. This study was carried on to find out how language learning Arabic online and challenges in learning the language at the Center for Language Development IAIN Padangsidimpuan. The research method applied a qualitative descriptive study. Participants were comprised of 178 students and lecturers at IAIN Padangsidimpuan Language Development Center academic year 2019/2020. Research instruments used were questionnaires, and documents from online learning screenshots. Analysis of this study employed the technique of presenting data in a narrative that resulted in the conclusion of the study. The results of this research indicated that the applications used in language teaching at the Center for Development Language were google classroom and WhatsApp. Barriers to learning are inadequate internet networks in a student residence. The biggest challenge of online learning is the lecturer and the students did not concentrate. Moreover, smartphones used in learning provided adverse effects on eye health and lack of interest in language learning. Lack of evaluation of learning and also lack time management that has been specified. A decrease in student achievement on speaking skill due to no reciprocal process orally in the learning process of faculty to students. There is a need for a new strategy at the Center for Language Development IAIN Padangsidimpuan so that learning objectives can be achieved. Lastly, the most important thing is that the preparation of digital facilities and infrastructure in implementing online language learning.